Assessment of the vegetation sensitivity index in alpine meadows with a high coverage and toxic weed invasion under grazing disturbance - Hu, Yi; Gou, Xiaowei; Tsunekawa, Atsushi; Cheng, Yunxiang; Hou, Fujiang (Frontiers in Plant Science, 2022)
Maintaining healthy ecosystems is essential to ensure sustainable socio-economic development. Studies combining remote sensing data with grassland health assessments, extensively performed at different scales, are important for monitoring grassland health from a spatiotemporal perspective to enable scientific grazing management. However, most studies only use quantitative grassland degradation indices, such as grassland cover; this is done despite the fact that some degraded grasslands maintain a high level of cover solely by virtue of the proliferation of toxic weeds. Thus, seeking indices that are a more accurate representation of the health status of grassland vegetation is of utmost importance. Therefore, in order to accurately characterize the ecological integrity of grasslands (i.e., while limiting the impact of confounding variables such as weeds), we chose the grassland health comprehensive evaluation index VOR (vigor, organization, and resilience) to assess the health of grasslands on the Tibetan Plateau. We extracted 11 commonly used vegetation indices based on remote sensing images to build a model, and then we applied the VOR evaluation index to two pastures on the Tibetan Plateau; the pastures exhibited different grazing intensities. Our results show that ecosystem health levels were lower in the central and southwestern parts of the lightly grazed pastures during the 2017–2018 growing season; whereas, the spatial distribution of health status of heavily grazed pastures was more even, but the value of VOR was lower than lightly grazed pastures. The proportion of healthy areas in lightly grazed pastures changed from 9% in July 2017 to 60% in August 2018, with significant improvements in vegetation health. The vegetation health of heavily grazed rangelands improved slightly in 2018. The ratio vegetation index was the most sensitive to the vegetation health response, enabling the quantification and prediction of regional vegetation health and objectively reflecting the actual condition of the grassland ecosystem. According to a multiple regression analysis, the main climatic limiting factor in the region is precipitation, which positively correlated with VOR; whereas, grazing disturbance is an important driving factor, and it is inversely correlated with VOR.